PERSEPSI MASYARAKAT MUSLlM TENTANG ZAKAT DI KOTA PALU - Faisal Attamimi (Hunafa: Jurnal Studia Islamika, 2008)
The purpose of this study was to analyze the perception of Muslim society of Palu  to  dhakâh. The method employed in this reserach was qualitative one. The teachniques of data collection employed was observation, interview and questionaire. The results of this research indicated that most of  Muslims of   Palu  percieved dhakâh as being an indivudual ibâdah so that they preferred distributing their dhakâh  individually to distributing it through  the BAZ (The Office of Collector and Distributor of Alms-Giving). The BAZ of  Palu could not be optimally managed because of (1) the lack of human resources; (2) the lack of Muslims’ knowledge of Palu about the essence of dhakâh, and (3) the ineffectiveness of dhakâh management of  the BAZ of Palu.Kata Kunci: persepsi, masyarakat muslim,  zakat,  Badan Amil Zakat